1996
DOI: 10.1007/bf02577636
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular liver biopsy: A review of 77 biopsies using a spring-propelled cutting needle (biopsy gun)

Abstract: Seventy-seven transjugular liver biopsies were performed with a coaxial, spring-loaded, 18-gauge cutting needle, the Biopty gun (Bard Biopsy System, Covington, GA, USA) on consecutive patients between July 1993 and February 1995. Fifty men and 27 women were included in the study; the mean age was 45 years (range 15-69 years). The average number of punctures per patient was 5.2, with a range of 2-9, yielding an average of 4.8 samples per patient (range 1-7). The length of the samples varied from 10 to 22 mm wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…A modified version of the percutaneous Vim-Silverman side-cutting needle -the trucut needle -has been proposed for TJLB with the aim of providing larger and less fragmented specimens (7,16,25) . An automated trucut needle, the Quick-Core needle system has also been proposed, and its success rate of histological diagnosis seems to be higher than the modified aspiration Ross needle in patients with suspicion of chronic liver diseases (2,9,12,18,19,20,27) .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A modified version of the percutaneous Vim-Silverman side-cutting needle -the trucut needle -has been proposed for TJLB with the aim of providing larger and less fragmented specimens (7,16,25) . An automated trucut needle, the Quick-Core needle system has also been proposed, and its success rate of histological diagnosis seems to be higher than the modified aspiration Ross needle in patients with suspicion of chronic liver diseases (2,9,12,18,19,20,27) .…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The risk of TJLBx is primarily related to intraperitoneal hemorrhage, which occurred in 0.35% of the 2271 cases reviewed by Colapinto [1]. Recent studies using cutting needles report complications rates ranging from 2% to 20% as reviewed by Gorriz et al [2]. Their study reported a complication rate of 13.4% which included all (minor and major) complications.…”
Section: Discussionmentioning
confidence: 96%
“…Failure to obtain a diagnosis in our nondiagnostic specimens was not due to fragmentation. Gorriz et al [2] had three cases that were non-diagnostic because of excessive fragmentation when using an 18-gauge biopsy gun.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In large series the Tru-cuttype liver biopsy systems have demonstrated a higher success rate than modified transseptal needles while maintaining the low complication rate of the transvenous access. Adequate specimens were obtained even in cirrhotic livers [10,11]. In the patient described, the right femoral route was chosen as this access seemed more convenient because of marked obesity.…”
Section: Discussionmentioning
confidence: 99%